A Qualitative analysis the Factors Affects Voters Behavior - Putu Ayu Suniadewi; Mansurni Abadi (Austronesia Akademika, 2025)
Understanding voter behavior in Indonesia's diverse sociopolitical landscape is critical for fostering democratic participation. This qualitative study examines the multifaceted factors influencing electoral choices in the 2024 Indonesian General Election through the lenses of sociological, psychological, and rational choice theories. Employing case studies, interviews, and thematic analysis of existing literature, the research highlights the interplay between Indonesia’s entrenched ethnic, religious, and social cleavages and emerging technological and demographic shifts. Key findings reveal a generational divide: urban, educated voters exhibit heightened skepticism toward institutional politics, while rural communities remain influenced by traditional patronage networks. The 2024 elections underscore the dual dynamics of digital campaign strategies such as the viral